Mental health and social interactions of older people with physical disabilities in England during the COVID-19 pandemic: a longitudinal cohort study - Andrew Steptoe, ProfDSc; Giorgio Di Gessa, PhD (Elsevier, 2021)
Summary: Background: The COVID-19 pandemic has affected mental health, psychological wellbeing, and social interactions. People with physical disabilities might be particularly likely to be negatively affected, but evidence is scarce. Our aim was to evaluate the emotional and social experience of older people with physical disabilities during the early months of the COVID-19 pandemic in England. Methods: In this longitudinal cohort study, we analysed data from the English Longitudinal Study of Ageing collected in 2018-19 and June-July, 2020, from participants aged 52 years and older and living in England. Physical disability was defined as impairment in basic and instrumental activities of daily living (ADL) and impaired mobility. Depression, anxiety, loneliness, quality of life, sleep quality, and amount of real-time and written social contact were assessed online or by computer-assisted telephone interviews. Comparisons of experiences during the COVID-19 pandemic of people with and without a physical disability were adjusted statistically for pre-pandemic outcome measures, age, sex, wealth, ethnicity, presence of a spouse or partner, number of people in the household, and chronic pain. All participants with full data available for both surveys were included in the analyses. Findings: Between June 3 and July 26, 2020, 5820 participants responded, 4887 of whom had full data available for both the pre-pandemic measures and the COVID-19 survey and were included in the analysis. During the COVID-19 pandemic, significantly more people with ADL impairment had clinically significant symptoms of depression (odds ratio 1·78 [95% CI 1·44-2·19]; p<0·0001), anxiety (2·23 [1·72-2·89]; p<0·0001), and loneliness (1·52 [1·26-1·84]; p<0·0001) than people without ADL impairment. Significantly more people with ADL impairment also had impaired sleep quality (1·44 [1·20-1·72]; p<0·0001) and poor quality of life than people without ADL impairment. The results were similar when disability was defined by impaired mobility. People with ADL impairment had less frequent real-time contact (0·70 [0·55-0·89]; p=0·0037) and written social contact (0·54 [0·45-0·64]; p<0·0001) with family than people without ADL impairment. Results for social contact were similar when disability was defined by impaired mobility. Interpretation: People with physical disability might be at particular risk for emotional distress, poor quality of life, and low wellbeing during the COVID-19 pandemic, highlighting the need for additional support and targeted mental health services. Funding: Economic and Social Research Council/UK Research and Innovation, National Institute on Aging, National Institute for Health Research.